PEMILIHAN TEKNOLOGI DAUR ULANG AIR LIMBAH DOMESTIK DI KANTOR BPPT - Yudo, Satmoko; Hernaningsih, Taty (Jurnal Air Indonesia, 2010)
The increasing variety of industrial activities in Indonesia resulted in ground water reserves in some areas experiencing drought. Exploitation of ground water by industry and the community in some big cities like Jakarta, resulting in the decrease of ground water and ground water quality reduced caused sea water instrusion. While the potential of wastewater produced by industrial and household waste high today. Based on the matters mentioned above and see the use of ground water that will be even greater in the future, then one of alternative that a lot of attention in many countries around the world are using wastewater reuse, particularly urban domestic wastewater (municipal wastewater) as a source of raw water for water supply. BPPT as a government office has made use of wastewater reuse technology, however, when the performance of the appliance is not working properly for it is necessary for re-evaluation and selection of wastewater reuse technology for better and sustainable.Ã‚Â Keywords : Wastewater Reuse Technology, Domestic Wastewater, Water Consumption Survey